Pengaruh Teknologi Informasi, Kualitas Sumber Daya Manusia, dan Pengendalian Internal terhadap Kinerja Instansi Pemerintah di Kabupaten Kampar - Rika Anisa; Agustiawan Agustiawan; Muhammad Ahyaruddin (CV. Ulil Albab Corp, 2024)
This research is a quantitative study designed to investigate the impact of information technology utilization, human resource quality, and internal control on the performance of government agencies within the Regional Government Organizations in Kampar Regency. The study uses purposive sampling, targeting heads of departments, heads of divisions, and secretaries from 53 regional government organizations in Kampar Regency, with a total of 53 respondents. A quantitative approach with a survey research type is employed, conducted both in-person and online via Google Forms. To ensure data quality, validity tests were administered, and normality tests were included as part of the classical assumption tests. Data analysis was carried out using multiple linear regression models. Hypothesis testing was conducted through partial tests (T-tests) and the coefficient of determination (R²). The findings reveal that information technology utilization and internal control significantly influence the performance of government agencies within the regional government organizations of Kampar Regency, while human resource quality negatively impacts their performance